Non-Isothermal Model of Ion Implantation with Combined Ion Beam; AIP Conference Proceedings; Vol. 1783 : Advanced Materials with Hierarchical Structure for New Technologies and Reliable Structures 2016 - Parfenova E. S. Elena Sergeevna (2016, 2016)
Title screen